Violence against women: Public policies and their paths of confrontation in primary care - Freire, Maria Antônia; Souza, Beatriz de Barros (Seven Editora, 2023)
The discussion about inequalities between men and women, as we know, is not recent, being common the belief, in Western history, that women were inferior in the metaphysical scale that divided human beings and, therefore, men had the right to exercise a public life in their place (MARTINS, 2015). DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-088